Lignin Sources and Uses: A Review - Fernando Jose Borges Gomes; Roberto Carlos Costa Lelis; Edva Oliveira Brito; Larisse Aparecida Ribas Batalha; Diana Catalina Cubides-Roman; Dalton Longue Junior; Iara Fontes Demuner; Fernando Almeida Santos; Rafael Eloy de Souza (Novel Aspects on Chemistry and Biochemistry Vol. 1, 2023)
The purpose of this brief review is to describe the structure of native lignin as well as the structure of technical lignin, including information about the different characteristics found on the market and the main pathways to treat it in applications as feedstock for bioproducts to obtain high added value products. The efficient use of renewable resources has emerged as a driving force for global industry seeking to improve competitiveness. Among the available natural raw materials, lignin, found in lignocellulosic biomass such as trees, is the only natural polymer with aromatic rings in its constitution. Annually, approximately 50 million tons of lignin are produced worldwide, with 98% to 99% of that amount incinerated to generate energy and steam in pulp mills. In a biorefinery concept, only a small fraction of the lignin recovered from the sulfite pulp mill is commercially recovered. According to recent research, technical lignin sources can also be used as feedstock for phenol derived products, technical carbons, fuels, and adhesives. However, some technological challenges must be overcome before these applications can be realized.